The Influence of Self-Compassion and Social Support on the Subjective Well-Being of Pesantren Teachers with Obedience to the Kiai as a Moderator - Bouti, Mohamad Rozkit; Shaleh, Abdul Rahman (Jurnal Psikologi Islam dan Budaya, 2026)
Everyone craves welfare, including Islamic boarding school (pesantren) teachers. In psychology, well-being relates to the subjective evaluation of feelings and life. This study aims to examine the influence of self-compassion and social support on the subjective well-being of pesantren teachers, with obedience to kiai as a moderator. Using purposive sampling, data were collected from 227 teachers across 11 Asshiddiqiyah pesantren branches. Measurements included adaptations of the Self-Compassion Scale Short Form (SCS-SF), Social Provisions Scale, Obedience to Authority Scale, and Scale of Positive and Negative Experience (SPANE). Data were analyzed using multiple regression analysis (MRA) with moderators via SPSS. Results showed a significant positive influence of self-compassion and social support on subjective well-being, which was moderated by obedience to kiai. These findings have implications for understanding how pesantren teachers fulfill their subjective well-being by paying attention to their level of compliance with the kiai.